Strategic Customer Relationship Management as a Tool to Strengthen Customer Interest in Islamic Banking: The Case of Bank Muamalat Metro Branch - Nur Khoiriyah, Siti (CV. HEI PUBLISHING INDONESIA, 2025)
Customer Relationship Management (CRM) is a strategic approach used by organizations to maintain effective communication and establish long-term relationships with customers. In the banking sector, high-quality service delivery plays a crucial role in building trust, enhancing corporate image, and attracting customer interest. This study aims to examine the Customer Relationship Management strategies implemented by Bank Muamalat KCP Metro in attracting customers. A qualitative descriptive research design was employed. Data were collected through semi-structured interviews and documentation, and analyzed using qualitative data analysis with an inductive approach. The findings indicate that the CRM strategies implemented by Bank Muamalat Indonesia KCP Metro are moderately effective. The bank has applied continuous service programs to maintain customer loyalty, implemented individualized service approaches based on customer needs and preferences (one-to-one marketing), and established cooperative partnerships with external institutions and companies beyond its core banking products through partnering programs. These strategies contribute to strengthening customer trust and increasing customer interest in Islamic banking services. The study provides practical insights into CRM implementation in Islamic banking institutions.